LITERATURE REVIEW: THE IMPLEMENTATION OF GREEN TAX IN INDONESIA FROM THE PERSPECTIVE OF ACCOUNTING AND SUSTAINABLE FISCAL POLICY - Astri Andaresta Darmanto; Vania Adeline Endrawati; Josephine Kurniawati Tjahjono (RISTANSI: Riset Akuntansi, 2026)
This study explores how environmental taxation (green tax) is implemented and reported in Indonesia, particularly in relation to sustainable fiscal policy and tax-related accounting practices. Adopting a qualitative descriptive literature review, the research synthesizes insights from national and international publications on green taxation, green accounting, and environmentally oriented fiscal frameworks. The review highlights that green taxes play a dual role: they act as economic tools for internalizing negative externalities and function as fiscal mechanisms to support long-term environmental financing. Although Indonesia has taken initial steps through the introduction of carbon taxation, several challenges remain, including regulatory gaps, institutional readiness, and the absence of explicit accounting standards governing environmental tax treatment. From an accounting perspective, integrating green taxes into both financial and sustainability reporting frameworks is crucial to enhancing transparency, accountability, and fiscal effectiveness. Overall, the study underscores the need for stronger alignment among fiscal policy, green accounting practices, and corporate governance to advance environmentally sustainable economic development.